Efektivitas Penggunaan Aplikasi CANVA sebagai Media Pembelajaran IPA MI/SD - Tri Wulandari; Adam Mudinillah (Jurnal Riset Madrasah Ibtidaiyah, 2022)
This article intends to describe the effectiveness of using Canva as an MI/SD science learning medium. Globalization brings major changes in the way people live. These changes are driven by the growing development of science and technology, which has an impact on various sectors of life, including in the field of education. The design of learning media at this time not only utilizes objects that can be found in everyday life but also utilizes the digital world. Canva is an application that can be developed in the process of making science learning media that really needs the media as an introduction to information from the content of abstract learning materials. The Canva application provides a variety of interesting features that can make it easier for teachers to create learning media, one of which is the availability of various templates that can be used in the process of designing learning media, one of which is science subjects in MI/SD. In carrying out this research, the literature review method was used, namely the process of placing, obtaining, reading, and evaluating various research literature related to or related to the issue to be studied. The data described are the results of research on the effectiveness of using the Canva application that has been carried out by previous researchers.